Influence of financial policy about the employment in Romania - Moşteanu Narcisa Roxana (Budgetary Research Review (BRR), 2011)
This paper aims to examine the influence of the fiscal and budgetary policy to the labour market and how to determine the movement of filled employment positions from one period to another, the gross job creation, the gross job destruction, the job reallocation and the average job vacancies. The paper draws especially on the data reflected National Institute of Statistics, for the period 2002 - 2009. Therefore the paper comes to show that measures of fiscal and budgetary policy are deeply involved within the labour market. In that respect this paper comes with pertinent solutions.
Keywords: E61; E62; E63; E64; E65; E66; 330; average job vacancies; gross job creation; gross job destruction; job reallocation; labour market; budgetary policy; fiscal policy